Diet and Chronic Non-Cancer Pain: The State of the Art and Future Directions - Katherine Brain (MDPI AG, 2021)
Nutrition plays an important role in pain management. Healthy eating patterns are associated with reduced systemic inflammation, as well as lower risk and severity of chronic non-cancer pain and associated comorbidities. The role of nutrition in chronic non-cancer pain management is an emerging field with increasing interest from clinicians and patients. Evidence from a number of recent systematic reviews shows that optimising diet quality and incorporating foods containing anti-inflammatory nutrients such as fruits, vegetables, long chain and monounsaturated fats, antioxidants, and fibre leads to reduction in pain severity and interference. This review describes the current state of the art and highlights why nutrition is critical within a person-centred approach to pain management. Recommendations are made to guide clinicians and highlight areas for future research.